Observation of the vortex ring state - Green, R.B.; Gilles, E.A.; Giuni, M.; Hislop, J.; Savas, O. (My University, 2014)
This paper considers the vortex ring state, a flow condition usually associated with the descent of a rotor into its own wake. The phenomenon is investigated through experiments on simple rotor systems, and a comparison is then made with observations of a flow generated by a specially designed open core, annular jet that generates a mean flow velocity profile similar to the mean flow in a rotor wake in hover. In an experimentally simulated descent, the jet flow generates a flow state that shares many features of the rotor vortex ring state.